Antibacterial effects of Quercus Brantii fruits and Stachys lavandulifolia methanol extracts on imipenemase-type metallo-beta lactamase-producing Pseudomonas aeruginosa - F. Shahi; A. Hashemi; Kh. Abdolmaleki; Z. Shahi; Sh. Amraei; H. Goudarzi; F. Fallah; S. Khoshnood (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Metallobeta-lactamase production is one of the most important mechanisms of antibiotic resistance. The aim of the present study was to evaluate the antibacterial activity of Stachys lavandulifolia and Quercus brantii on the IMP-type metallo-beta-lactamase-producing Pseudomonas aeruginosa. Methods: This study was performed on burn patients between January 2015 and November 2015. Susceptibility to the antibiotics and methanol extracts were evaluated by broth microdilution and disc diffusion methods. MBL-producing P. aeruginosa was detected by Combination Disk Diffusion Test (CDDT). The bla (VIM) and bla (IMP) genes detection were performed by PCR and sequencing methods. Results: Forty eight (57.9%) of 83 P. aeruginosa strains were resistant to imipenem and were blaIMP-1 genes positive, whereas none were bla (VIM) genes positive. In the hospitalized patients with MBL-producing Pseudomonas infection, the mortality rate was 4.48 (8.3%). It was found that S. lavandulifolia extract showed a high antibacterial effect on regular and IMP-producing P. aeruginosa strains at the concentration of 0.625 mg/mL, but Q. Brandy extract showed no antibacterial effect in the tested concentration. Conclusion: In burn patientsMBL-producing P. aeruginosa has been found in high incidence. Detection of this pseudomonas and determination of drug resistance pattern is very important. The methanol extract of S. lavandulifolia showed suitable effects on MBL-producing P. aeruginosa in vitro; therefore, it could be suggested for further studies against carbapenem resistant P. aeruginosa isolates.